PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN HONDA REVO PADA CV LION KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - SINYO, STANLEY; MONTOLALU, JOHNY; WALANGITAN, OLIVIA F.CH. (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. The increasingly fierce competition is inevitable in the business world, but it is a challenge that must be faced. A wide variety of ways in which to dominate the market, one of them by creating a quality product in order to attract consumers in making purchasing decisions. This study aims to determine how much influence consumer behavior towards Honda Revo Product Purchasing Decisions in District Jailolo. To answer the purpose of this study used statistical parametric analysis tools such as correlation and regression. The results showed consumer behavior has a significant influence on purchasing decisions. Thus, it is expected CV Lion must pay attention to consumer behavior Products Honda Revo order to give effect to the purchase decision. Keywords:Consumer Behavior, Purchasing Decisions